?Removal of Iron and Manganese from Under- ground Water Using Cement Dust - KHATER, EM.H. (Biological Sciences - PJSIR, 1996)
Cement dust contains basically amixture ofraw materials used in the cement production, clinker nearly amorphous and some volatile components [4,5]. Many reports have revealed that cement dust can be utilized as fertilizer [6,7], bituminous filler, lime replacement and an additive in clay brick industry [4]. Salem [8] has reported that cement dust can be used to purify a highly contaminated water with the aim of evaluating the possibility to attenuate the toxicity given by the presence of heavy metals.